The NASA Ames PAH IR Spectroscopic Database: Computational Version 3.00 with Updated Content and the Introduction of Multiple Scaling Factors - Bauschlicher, Charles W.; Ricca, A.; Boersma, C.; Allamandola, L. J. (The Astrophysical journal. Supplement series, 2018)
Version 3.00 of the library of computed spectra in the NASA Ames PAH IR Spectroscopic Database (PAHdb) is described. Version 3.00 introduces the use of multiple scale factors, instead of the single scaling factor used previously, to align the theoretical harmonic frequencies with the experimental fundamentals. The use of multiple scale factors permits the use of a variety of basis sets; this allows new PAH species to be included in the database, such as those containing oxygen, and yields an improved treatment of strained species and those containing nitrogen. In addition, the computed spectra of 2439 new PAH species have been added. The impact of these changes on the analysis of an astronomical spectrum through database-fitting is considered and compared with a fit using Version 2.00 of the library of computed spectra. Finally, astronomical constraints are defined for the PAH spectral libraries in PAHdb.